A Study to Evaluate Change in Ventricular Volume Obtained by Cranial Distraction for Craniosynostosis. (May 2019) - Hashmi, Asra; Davis, Greta; Zaldana, Michelle; Vinocur, Daniel; Cahill, Gabrielle L.; Brandel, Michael G.; Lance, Samuel; Meltzer, Hal S.; Gosman, Amanda A.
Abstract : Background: The aims of the current analysis were to study the change in ventricular volume (VV) obtained with cranial distraction in patients with craniosynostosis and compare it with the change in total intracranial volume (ICV) and brain volume. Methods: After institutional review board approval, a retrospective review was performed on patients undergoing cranial distraction over a 5-year period. GE Healthcare AdW 4.3 volume assessment software was utilized to calculate preoperative and postdistraction ICV, VV, and whole-brain volume. Data were also collected on patient demographics, age at the time of distraction, time spent in distraction and consolidation, and length of stay. t Tests were used for comparison. Results: Twenty-three patients met our inclusion criteria. Forty-eight percent of patients (n = 11) had right-sided cranial distraction, 30% (n = 7) had bilateral distraction, and 22% of patients (n = 5) had left-sided distraction. At the preoperative stage, mean head circumference was 42.5 ± 4.7 cm, mean ICV was 810.1 ± 27 cm 3, mean non-VV (NVV) was 796.2 ± 268 cm 3, and mean VV was 13.9 ± 9 cm 3 . After a mean of 27.4 mm of distraction, occurring over a mean of 26 days and consolidation period of 149 days, a second computed tomography scan was obtained. Mean postdistraction head circumference was 49.1 ± 3.9 cm, mean ICV was 1074.1 ± 203 cm 3, mean NVV was 1053.5 ± 197 cm 3, and VV was 20.6 ± 14 cm 3 . Mean % increase in ICV at this stage was 47.4%; mean % NVV increase was 48.5% as opposed to 60.3% increase in VV. Conclusions: Cranial distraction is known to effectively increase ICV. Our study suggests that the effect of this volumetric increase is much more pronounced on the VV compared with the brain volume. Further studies are underway to investigate whether this short-term marked increase in VV is sustained over a long-term period.